2009
DOI: 10.1002/hep.23102
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to liver fibrosis in mice expressing a connective tissue growth factor transgene in hepatocytes

Abstract: Connective tissue growth factor (CCN2) is a matricellular protein that is up-regulated in many fibrotic disorders and coexpressed with transforming growth factor ␤. CCN2 promotes fibrogenesis and survival in activated hepatic stellate cells, and injured or fibrotic liver contains up-regulated levels of CCN2 that are produced by a variety of different cell types, including hepatocytes. To investigate CCN2 action in vivo, transgenic FVB mice were created in which the human CCN2 gene was placed under the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 34 publications
6
73
0
1
Order By: Relevance
“…d HSC maintained in 0.5% FCS showed upregulation of CCN2/CTGF when cells were infected with an adenovirus driving expression of CCN3/NOV. Please note that the stimulation with TGF-β induced CCN2/CTGF expression in HSC e CCN3/NOV overexpression slightly decreased TGF-β-induced collagen type I and α-SMA expression, while remarkably both CCN2 and CCN3 significantly reduced TIMP-1 collagen type I and α-SMA expression, a finding that is in line with a previous report showing that elevated CCN2/ CTGF levels in hepatocytes of transgenic mice in vivo does not cause hepatic injury or fibrosis per se but renders the liver more susceptible to the injurious actions of other fibrotic stimuli (Tong et al 2009). …”
Section: Resultssupporting
confidence: 90%
“…d HSC maintained in 0.5% FCS showed upregulation of CCN2/CTGF when cells were infected with an adenovirus driving expression of CCN3/NOV. Please note that the stimulation with TGF-β induced CCN2/CTGF expression in HSC e CCN3/NOV overexpression slightly decreased TGF-β-induced collagen type I and α-SMA expression, while remarkably both CCN2 and CCN3 significantly reduced TIMP-1 collagen type I and α-SMA expression, a finding that is in line with a previous report showing that elevated CCN2/ CTGF levels in hepatocytes of transgenic mice in vivo does not cause hepatic injury or fibrosis per se but renders the liver more susceptible to the injurious actions of other fibrotic stimuli (Tong et al 2009). …”
Section: Resultssupporting
confidence: 90%
“…Furthermore, transgenic mice expressing CTGF under the control of the albumin gene promoter showed exacerbation of liver fibrosis induced by chronic CCl 4 administration (49), demonstrating that hepatocytederived CTGF plays an important role in liver fibrogenesis. However, Tong et al (49) have also reported that hepatocyte-specific CTGF transgenic mice did not show spontaneous fibrosis in the liver without any fibrotic stimuli. Taken together, these findings support the idea that CTGF produced from hepatocytes may be an important factor for promoting liver fibrosis in the presence of apoptotic stimuli in Mdm2-knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, increased fibrosis was observed in mice with liver-specific CCN2 overexpression, but only upon tissue injury. This observation suggests that perhaps induced inflammatory mediators could interact with CCN2 to promote increased fibrosis or that the inflammatory microenvironment could change the response of cells to CCN2 (40). This is relevant because CCN2 levels are elevated during disc degeneration, a condition characterized by tissue inflammation (23).…”
Section: Discussionmentioning
confidence: 99%